The Relationship Between Customer Satisfaction and Service Quality of the Kuwait Airways (KU) - AL-Mutairi, Abdullah; Naser, Kamal; Simintiras, Antonis; Fayez, Fatema (Journal of Ecohumanism, 2024)
This research sought to determine the SERVQUAL dimensions that have been commonly referenced in earlier studies, namely tangibility, empathy, assurance, reliability, and responsiveness, and to evaluate their impact on KU customer satisfaction. To fulfill the objectives of the study, two hundred structured questionnaires were distributed among KU customers, yielding 155 completed responses, which corresponds to a usable response rate of 77.5%. The analysis of the collected data indicates that passengers prioritize the dimensions of assurance, tangibility, and responsiveness, with assurance being recognized as the most significant factor influencing the service quality of KU. Furthermore, the findings suggest that customer satisfaction is influenced by the demographic characteristics of the respondents. The analysis underscores the importance for decision-makers to focus on aspects within the assurance, tangibility, and responsiveness dimensions of SERVQUAL to enhance customer satisfaction and loyalty.